2015
DOI: 10.1021/acs.jpcc.5b00849
|View full text |Cite
|
Sign up to set email alerts
|

Dark Photoswitching Induces Coulomb Blockade Diamond Collapse

Abstract: A derivative of the photochromic molecule dihydroazulene (DHA) undergoes bias-induced switching into its vinylheptafulvene (VHF) conformation when inserted into a silver junction. This dark switching mechanism, which induces a collapse of the Coulomb blockade diamonds, is explained by quantum calculations on the molecular transport junction. Analysis of the nonequilibrium populations of molecular redox states explains the observed bias threshold. Predictions are made that another DHA derivative will not, in fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…In a stability plot, the single‐molecule conductance is represented by a specific color code as a function of gate ( x ‐axis) and bias ( y ‐axis) potentials. In the Coulomb blockade regime, diamond‐shaped islands of no conductance are observed, corresponding to a specific redox state of the molecule . These Coulomb blockade diamonds may be influenced by a dark photoswitching event as the diamond of the switching state may collapse (i.e., resulting in a decrease in diamond size) or explode (i.e., resulting in an increase in diamond size).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a stability plot, the single‐molecule conductance is represented by a specific color code as a function of gate ( x ‐axis) and bias ( y ‐axis) potentials. In the Coulomb blockade regime, diamond‐shaped islands of no conductance are observed, corresponding to a specific redox state of the molecule . These Coulomb blockade diamonds may be influenced by a dark photoswitching event as the diamond of the switching state may collapse (i.e., resulting in a decrease in diamond size) or explode (i.e., resulting in an increase in diamond size).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent experiments have shown that the switching mechanism of some photoswitches in a junction also can be promoted by a voltage stimulus, thus without a light stimulus . The process was named dark photoswitching due to the paradoxical behaviour of a photoswitch switching without light.…”
Section: Introductionmentioning
confidence: 99%
“…In the Coulombb lockade regime, diamond-shaped islands of no conductance are observed, corresponding to as pecific redox state of the molecule. [11,17] These Coulombb lockade diamonds may be influenced by ad ark photoswitching event as the diamond of the switching state may collapse (i.e.,r esulting in ad ecrease in diamond size) or explode (i.e.,r esulting in an increasei nd iamond size). The physics behind ac ollapse and an explosion of ad iamond is dependent on the electron affinities (EA) and ionization potentials (IP) of two isomers,s ince the heighto fadiamond can be expressed as the sum of EA and IP times ac onstant( see the Computational section).…”
Section: Manifestation Of Switchingmentioning
confidence: 99%
“…However,r ecent experiments have shown that the switching mechanism of some photoswitches in aj unction also can be promoted by av oltage stimulus, thus withoutal ight stimulus. [10,11] The process was named dark photoswitching due to the paradoxical behaviour of ap hotoswitch switching without light. Dark photoswitching was observed for ad ihydroazulene derivative( DHA) operating in the Coulomb blockader egime, [10] where the switching from DHA into its photo-isomer vinylheptafulvene (VHF) was observed by the change of the conductance properties.…”
Section: Introductionmentioning
confidence: 99%
“…The recent extension of the QM/FQ model to analytical first and second derivatives for Hartree-Fock (HF) and Kohn-Sham (KS) methods [37] and to the corresponding response equations for various internal and external perturbations [38,39] makes this model particularly suitable for the evaluation of molecular properties and spectroscopic parameters. Use of polarizable QM/MM models (hereafter referred to as polarizable embedding [PE]) becomes even more significant for excited electronic states and has been considered by several groups [39][40][41][42][43] since the pioneering work by Luzhkow and Warshel exploiting the Langevin dipole solvent model. [44] However, to the best of our knowledge, those studies have been limited to excitation energies or excitation energy transfers, whereas excited state structures have never been addressed so far, not to speak about vibronic contributions.…”
Section: Introductionmentioning
confidence: 99%